Economic Evaluation Of Respiratory Medication Therapy Adherence Clinic (Rmtac) On Asthma Patients In Malaysia - Yong, Yee Vern (2016)
This study aimed to evaluate the cost-effectiveness of a pharmacist-led respiratory clinic as an adjunct to the usual physician care (rmtac), versus usual physician care alone (usual care clinic). A dynamic adherence asthma markov cohort model was developed. The economic evaluation was based on a lifetime horizon and cycle length of one month, from the healthcare providers (ministry of health) perspective, with the outcomes assessed in cost per qaly gained and cost per hospitalization averted. Probabilities of asthma control-adherence states from rmtac database, costs from public sources, utilities using standard gamble method on malaysia’s asthma patients, and other inputs from secondary data sources were used to inform the probabilistic model. Subgroup analysis was conducted against 30 and 70-year old cohorts. Scenario analyses were conducted to evaluate the structural and methodological uncertainties of the model. In the economic evaluation, rmtac was found to be cheaper and more effective, at an icer of -rm9,862.65 (-25,833.49 — (-3,711.69)) per qaly gained and -rm1,358.68 (-1,686.11 — (-924.31)) per hospitalization averted.